2013
DOI: 10.3758/s13423-013-0501-5
|View full text |Cite
|
Sign up to set email alerts
|

Dual-learning systems during speech category learning

Abstract: Dual-systems models of visual category learning posit the existence of an explicit, hypothesistesting 'reflective' system, as well as an implicit, procedural-based 'reflexive' system. The reflective and reflexive learning systems are competitive and neurally dissociable. Relatively little is known about the role of these domain-general learning systems in speech category learning. Given the multidimensional, redundant, and variable nature of acoustic cues in speech categories, our working hypothesis is that sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
137
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(142 citation statements)
references
References 36 publications
5
137
0
Order By: Relevance
“…In the visual domain, it has been suggested that full feedback discourages learners from switching to using inseparable boundaries, rather than separable boundaries, to approximate the category structure (Maddox et al, 2008). The disruptive effect of full feedback has been replicated in speech category learning, where the optimal decision boundaries are posited to be inseparable (Chandrasekaran et al, 2014a;Chandrasekaran et al, 2014b;Maddox and Chandrasekaran, 2014). One possible explanation for the equivalent performance between full and minimal feedback conditions in the auditory domain is that the learners were less likely to be initially biased towards using separable boundaries, when learning less easily verbalizable non-speech auditory categories than with speech auditory categories.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In the visual domain, it has been suggested that full feedback discourages learners from switching to using inseparable boundaries, rather than separable boundaries, to approximate the category structure (Maddox et al, 2008). The disruptive effect of full feedback has been replicated in speech category learning, where the optimal decision boundaries are posited to be inseparable (Chandrasekaran et al, 2014a;Chandrasekaran et al, 2014b;Maddox and Chandrasekaran, 2014). One possible explanation for the equivalent performance between full and minimal feedback conditions in the auditory domain is that the learners were less likely to be initially biased towards using separable boundaries, when learning less easily verbalizable non-speech auditory categories than with speech auditory categories.…”
Section: Discussionmentioning
confidence: 90%
“…In the auditory domain, the presence of feedback has been shown to enhance speech category learning in two investigations, but full and minimal feedback conditions could not be compared, as there were only two possible categories (Goudbeek et al, 2008;McCandliss et al, 2002). Full and minimal feedback conditions have been compared in speech category learning with four categories, but generalizability was limited, as the relevant dimensions had not been constrained by the experimenters (Chandrasekaran et al, 2014b). The current study is the first to suggest that non-speech auditory categories with separable optimal decision boundaries can be learned faster with full, relative to minimal, feedback.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the presentation of the various tokens during the task may have allowed listeners to track the statistical distributions of the two categories (e.g., Maye and Gerken, 2000), and participants in the present study may have been able to utilize this information to improve their performance on both tasks. However, some studies have shown that learners typically rely on explicit strategies in early stages of the learning process (e.g., Chandrasekaran et al, 2014); therefore, implicit learning may not be helpful to participants at this point. If it is the case that participants are learning from the discrimination task, we argue that the Two Vowel group had more opportunities to learn because they received twice as many tokens in the discrimination assessments and should therefore show more improvement.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, effective processing of speech is likely to be rather automatic and not require extensive effortful processing. In fact, Chandrasekaran and colleagues have proposed that successful learning of non-native speech sound contrasts is most evident in individuals who shift to implicit, procedural processing systems early in learning (Chandrasekaran, Yi & Maddox, 2014). In the next section, we will consider how declarative and procedural systems are affected by sleep -a factor which is known to affect learning in other domains, but is relatively unexplored in non-native speech sound learning.…”
Section: Neural Pathways For Non-native Speech Sound Learningmentioning
confidence: 96%